Comparison of aerial conidia and blastospores from two entomopathogenic fungi against Diaphorina citri (Hemiptera: Liviidae) under laboratory and greenhouse conditions. Issue 8 (3rd August 2018) - Morales-Reyes, Celso; Mascarin, Gabriel Moura; Jackson, Mark Alan; Hall, David; Sánchez-Peña, Sergio R.; Arthurs, Steven Paul
ABSTRACT: This study compared the insecticidal activity of liquid culture-produced blastospores and solid substrate-produced aerial conidia of Beauveria bassiana GHA and Isaria fumosorosea ARSEF3581 strains against Diaphorina citri adults. Insects exposed to 10 7 propagules/ml in a spray residue contact leaf bioassay died within 6 days at 25°C, with no significant differences between fungal treatments. At higher concentrations (10 8 propagules/ml), I. fumosorosea conidia killed psyllids faster compared to its blastospore formulation, i.e. 4 versus 5 days, respectively. In greenhouse tests, the same treatments applied to infested citrus plants (2 × 10 6 spores/ml) all significantly reduced the number of nymphs compared with the untreated controls over 3 weeks; however, only I. fumosorosea blastospores significantly reduced the number of F1 adult psyllids when compared with controls. Similar results were observed in the follow-up greenhouse test, where I. fumosorosea blastospores were the most effective treatment overall, reducing D. citri populations by about 60% after 21 days; by contrast, imidacloprid killed almost 100% of psyllids within a week in both tests. Fewer psyllids exhibited mycosis in the greenhouse (i.e. ≈20 versus ≥ 87% in the laboratory). This is the first report comparing both conidial and blastospore formulations of B. bassiana and I. fumosorosea for the control of a psyllid pest. Field testing is required to determine how successful different spore formulations might be under various environmental conditions.